If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1x = 2x + -6 Reorder the terms: 2 + -1x = -6 + 2x Solving 2 + -1x = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + -1x + -2x = -6 + 2x + -2x Combine like terms: -1x + -2x = -3x 2 + -3x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + -3x = -6 + 0 2 + -3x = -6 Add '-2' to each side of the equation. 2 + -2 + -3x = -6 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = -6 + -2 -3x = -6 + -2 Combine like terms: -6 + -2 = -8 -3x = -8 Divide each side by '-3'. x = 2.666666667 Simplifying x = 2.666666667
| 3m^2-6m=9 | | 4.5(x+5.5)=4.5(x+5.5) | | 13t+10=-3 | | 5t+6=26 | | x^3=6x+x^2 | | 26+3y-3=15y-12-5y | | 5a-10=-5a | | 6v^2+252=78v | | 12y+164=7.6 | | 50t^2+80t+32= | | 0.18y+0.02(y+6000)=1120 | | 1-3/5=-1/5 | | -3(-2)+4= | | 5m^2-18M+9=0 | | -5/2t=4 | | -19(-2)= | | 6c-a/7=b | | 9m+3m-10=3(3m+3) | | 10=4k+6 | | x+20+3x=-15-3x-21 | | 1=c/4-2 | | 5(y-5)+8= | | 3(1+2x)-x=28 | | 19b=90 | | 1=c/4--2 | | 4x+(8x+48)=180 | | 9(5x+1)=4x-7x | | 4f+2=2(2f+3) | | 3-3v=18 | | 5x+2.3y=-18 | | -5m+22-2(m-1)=7m-(9m-5)-2m+7 | | 4x-2x-(-9)=3x-2x-4.37 |